PENGARUH PENGETAHUAN, RELIGIUSITAS, DAN SERTIFIKASI HALAL TERHADAP HALAL TRACEABILITY DENGAN HALAL AWARENESS SEBAGAI VARIABEL INTERVENING (Studi Kasus Pedagang Muslim Di Pasar Tradisional Kota Malang) - Farida Diyan Pertiwi; Maslichah Maslichah; M Cholid Mawardi (Fakultas Ekonomi dan Bisnis Universitas Islam Malang, 2022)
The objective of this paper is to analyze the role of halal awareness, employing variables that canbe both influential (determinant) and influenced (output). The purpose of this paper is to consider howhalal awareness affects the halal traceability of products from the perspective of a business actor. Halalproducts are important in a country with the largest Muslim population. However, there are still manypeople who are not aware of the halalness of the product so that there are many products that are not yetclear about the halalness of the product. Questionnaires were distributed directly and data werecollected from 105 entrepreneurs. SEM-PLS was then applied to analyze the data. The results show thathalal awareness and the halal traceability influenced the business actors. Meanwhile, the halalawareness of the business actors was influenced by halal certification and religiosity. Knowledge failedto influence halal awareness.